The Ontology of Tattoos And Memory: A Psychological Reading of The Body of Biography In Milawa of Abdelkader Fidouh (Journal of the College of Basic Education, 2026)
We base this psychological approach on one of the most recent works by the Algerian critic Abdelkader Fidouh, his autobiography entitled "Milawa, A Biography of the Soul's Confessions," a psychological reading according to the psychological approach. Milawa is written in a poetic language without exaggeration, and we will examine the mechanisms of the psychological approach to the criticism of Arabic poetry, drawing from the author's own work. This psychological reading is not that which emerges from the clinical setting of psychoanalysis, but rather aims to encompass the psychological aspects of human behavior.We will apply some mechanisms that examine the literary work from a psychological perspective, exploring the psychological significance of place, the psychological dimensions of imagery, and concluding with a study of the psychological function of autobiographical narrative.